The formalized assessment of a reputational capital for a region in Tatarstan - Leonid Alekseevich Elshin, Marat Rashitovich Safiullin, Alexander Stanislavoich Grunichev, (Opción, 2019)
A key feature of the study is the proposed preliminary version of the conceptual approach to quantifying the reputational capital of a territory, which allows for a transition from qualitative assessments of the evolution of the process under study and its impact on key development parameters of macroeconomic indicators. The obtained data demonstrate the increasing wavy trend of the region’s reputation due to the different directions of changes in the behaviour of the key sub-indices values. In conclusion, the proposed tools for assessing the reputational capital of territories significantly bring us up to the solution of the set task.